The Effects of Entrepreneurship Education - Richard Weber; Georg von Graevenitz; Dietmar Harhoff (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2009)
Entrepreneurship education ranks highly on policy agendas in Europe and the US, but little research is available to assess its impacts. In this context it is of primary importance to understand whether entrepreneurship education raises intentions to be entrepreneurial generally or whether it helps students determine how well suited they are for entrepreneurship. We develop a theoretical model of Bayesian learning in which entrepreneurship education generates signals which help students to evaluate their own aptitude for entrepreneurial tasks. We derive predictions from the model and test them using data from a compulsory entrepreneurship course at a German university. Using survey responses from 189 students ex ante and ex post, we ?nd that entrepreneurial propensity declined somewhat in spite of generally good evaluations of the class. Our tests of Bayesian updating provide support for the notion that students receive valuable signals and learn about their own type in the entrepreneurship course.
urn:nbn:de:bvb:19-epub-13283-1
Keywords: 330; entrepreneurship; entrepreneurship education; Bayes' Rule; learning; signals; Betriebswirtschaftsstudium; Führungskräfteentwicklung; Lehrplan; Entrepreneurship-Ansatz; Wirkungsanalyse; Test; Bayes-Statistik